Electrical Muscle Stimulation Accelerates Functional Recovery After Nerve Injury. (1st February 2020) - Fu, Tengfei; Jiang, Libo; Peng, Yi; Li, Zheng; Liu, Shuhao; Lu, Junren; Zhang, Feng; Zhang, Jian
Highlights: Electrical muscle stimulation accelerates axon regeneration and functional recovery following nerve injury. Electrical muscle stimulation promotes autophagy flux in distal nerve segments after nerve injury. Inhibition of autophagy abolishes the positive effect of electrical muscle stimulation on nerve injury. Abstract: Electrical muscle stimulation has been demonstrated to facilitate nerve regeneration and functional recovery, but the underlying mechanism remains only partially understood. In this study, we investigated the positive effect of electrical muscle stimulation following nerve injury and its molecular mechanisms of autophagy regulation. The sciatic nerves of Sprague-Dawley rats were transected and immediately repaired. Gastrocnemius muscles were electrically stimulated using surface electrodes. Motor functional recovery was assessed by gait analysis, nerve conduction examination and histological appearance of the target muscle. Axon regeneration was investigated by morphometric analysis. Western blotting and immunofluorescence staining were used to detect the expression of molecular biological changes in distal nerve stump. Ultrastructural features of the nerve were evaluated by transmission electron microscope. We found that axon regeneration and motor functional recovery were improved by electrical muscle stimulation. The number of autophagosomes and the expression of autophagy marker LC3-Ⅱ in distal nerve stump were increased while the level of autophagy substrate protein P62 was decreased following electrical muscle stimulation. Blockage of the autophagy flux by chloroquine (CQ) diminished the positive effect of electrical muscle stimulation on nerve injury. These results illustrated that electrical muscle stimulation accelerates axon regeneration and functional recovery through promoting autophagy flux in distal nerve segments following nerve injury and immediate repair (IR) by a so far unknown mechanism.